Asynchronous event-based sampling data for impulsive protocol on consensus of non-linear multi-agent systems. (July 2019) - Han, Yiyan; Li, Chuandong; Zeng, Zhigang
Abstract: In this paper, we discuss the consensus problem of non-linear multi-agent systems where an impulsive protocol with event-based asynchronously sampled data is adopted. Systems that communicate by data asynchronously sampled in limited time intervals are constructed. By separating time instants at which the sampling and communication occur into different ones, resources for such activations that every agent must execute can be reallocated to reduce the system load at communication instants. Event-based schemes are introduced to manipulate the sampling behavior. Two cases that with and without leader in directed networks topologies are both investigated. Sufficient conditions for system parameters and the event-based sampling schemes are given to guarantee the consensus. Numerical simulations are presented to illustrate the effectiveness of our proposed method.